``Heraldyka'' - Archiwum Biblioteki Kórnickiej (1869-1923); Baer Joseph & Co., |Buchhandlung Frankfurt n. M.; Biblioteka Kórnicka; Hiersemann Karl W., |Buchhandlung Lipsk; Jolowicz Józef, |Księgarnia Poznań (1916)
Baer Joseph & Co., Frankfurt n. M., k. 1. - Hiersemann Karl W., k. 4. - Jolowicz Józef, k. 2. - Nieciszewski, k. 5.
1000,00
Keywords: Frankfurt n. M; księgarnia - Baer Joseph & Co; Lipsk; księgarnia - Hiersemann Karl W; Poznań; księgarnia - Jolowicz Józef; Heraldyka; Korespondencja; Księgarnie